Perioperative antimicrobial prophylaxis in adult patients: The first multicenter clinical practice audit with intervention in Greek surgical departments. (17th June 2021) - Chorafa, Elisavet; Iosifidis, Elias; Tsiodras, Sotirios; Skoutelis, Athanasios; Kourkouni, Eleni; Kopsidas, Ioannis; Tsopela, Grammatiki-Christina; Chorianopoulou, Evangelia; Triantafyllou, Christos; Kourlaba, Georgia; Zaoutis, Theoklis; Roilides, Emmanuel
Abstract: Objective: To audit clinical practice and implement an intervention to promote appropriate use of perioperative antimicrobial prophylaxis (PAP). Design: Prospective multicenter before-and-after study. Setting: This study was conducted in 7 surgical departments of 3 major Greek hospitals. Methods: Active PAP surveillance in adults undergoing elective surgical procedures was performed before and after implementation of a multimodal intervention. The surveillance monitored use of appropriate antimicrobial agent according to international and local guidelines, appropriate timing and duration of PAP, overall compliance with all 3 parameters and the occurrence of surgical site infections (SSIs). The intervention included education, audit, and feedback. Results: Overall, 1, 447 patients were included: 768 before and 679 after intervention. Overall compliance increased from 28.2% to 43.9% ( P = .001). Use of antimicrobial agents compliant to international guidelines increased from 89.6% to 96.3% ( P = .001). In 4 of 7 departments, compliance with appropriate timing was already >90%; an increase from 44.3% to 73% ( P = .001) and from 20.4% to 60% ( P = .001), respectively, was achieved in 2 other departments, whereas a decrease from 64.1% to 10.9% ( P = .001) was observed in 1 department. All but one department achieved a shorter PAP duration, and most achieved duration of 2 days. SSIs significantly decreased from 6.9% to 4% ( P = .026). After the intervention, it was 2.3 times more likely for appropriate antimicrobial use, 14.7 times more likely to administer an antimicrobial for the appropriate duration and 5.3 times more likely to administer an overall appropriate PAP. Conclusion: An intervention based on education, audit, and feedback can significantly contribute to improvement of appropriate PAP administration; further improvement in duration is needed.